2009
DOI: 10.1165/rcmb.2008-0410oc
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Peptidase Inhibitor 3 (Elafin) Are Associated with Acute Respiratory Distress Syndrome

Abstract: Peptidase inhibitor 3 (PI3, elafin) is a protease inhibitor produced locally in the lung, where it plays a central role in controlling excessive activity of neutrophil elastase. Our previous study revealed that PI3 gene expression is down-regulated during the acute stage of acute respiratory distress syndrome (ARDS). We conducted a casecontrol study to investigate whether genetic variants in PI3 gene are associated with ARDS development. Based on resequencing data from 29 unrelated white subjects, three taggin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 37 publications
2
24
1
Order By: Relevance
“…Assuming dominant and additive models of inheritance, and after adjustment by age, sex, and APACHE III score, we observed a significant association between the minor allele of rs2664581 (C allele) and an increased risk of ARDS (OR = 1.50, 95% CI = 1.07-2.12, P = 0.0198 and OR = 1.35; 95% CI = 1.01-1.80, P = 0.0426, for the dominant and additive models, respectively). The direction and magnitude of association was the same as previously observed (21). Stratified analyses showed a stronger effect of PI3 variants on ARDS susceptibility among the subjects with sepsis (OR = 1.51, 95% CI = 1.04-2.18, P = 0.0297 and OR = 1.44, 95% CI = 1.04-1.99, P = 0.0276, for the dominant and additive models, respectively; Table 3 (29), was validated in the current study using a cohort including mild to severe ARDS (Pa O 2 /FI O 2 < 300 mm Hg with PEEP > 5 cm H 2 O, formerly ALI).…”
Section: Association Of Pi3 Variant Rs2664581 With Risk Of Ardssupporting
confidence: 71%
See 2 more Smart Citations
“…Assuming dominant and additive models of inheritance, and after adjustment by age, sex, and APACHE III score, we observed a significant association between the minor allele of rs2664581 (C allele) and an increased risk of ARDS (OR = 1.50, 95% CI = 1.07-2.12, P = 0.0198 and OR = 1.35; 95% CI = 1.01-1.80, P = 0.0426, for the dominant and additive models, respectively). The direction and magnitude of association was the same as previously observed (21). Stratified analyses showed a stronger effect of PI3 variants on ARDS susceptibility among the subjects with sepsis (OR = 1.51, 95% CI = 1.04-2.18, P = 0.0297 and OR = 1.44, 95% CI = 1.04-1.99, P = 0.0276, for the dominant and additive models, respectively; Table 3 (29), was validated in the current study using a cohort including mild to severe ARDS (Pa O 2 /FI O 2 < 300 mm Hg with PEEP > 5 cm H 2 O, formerly ALI).…”
Section: Association Of Pi3 Variant Rs2664581 With Risk Of Ardssupporting
confidence: 71%
“…Our previous genome-wide expression analysis showed that PI3 gene expression is downregulated during the acute stage of ARDS, and this correlates well with plasma preelafin levels (20). Recently, we found that single-nucleotide polymorphism (SNP) rs2664581, located in exon 2 of PI3 gene, is associated with increased ARDS risk and pre-elafin circulating levels (21). This SNP results in an amino acid substitution (Thr34Pro) within the N-terminal (cementoin) domain of pre-elafin, which anchors the molecule to extracellular matrix (ECM) proteins (22)(23)(24)(25).…”
Section: Clinical Relevancementioning
confidence: 97%
See 1 more Smart Citation
“…1,2 Since the first description of ALI/ARDS, in 1967, numerous studies have been conducted to better understand the pathogenesis. 3,4 Exposure to hazardous factors such as acid, lipopolysaccharide, hyperoxia, or overinflation generates excessive levels of reactive oxygen species (ROS) and recruitment of considerable amounts of neutrophils in lung tissue, thus resulting in proinflammatory processes and eventually cellular, and tissue dysfunction, which contributes to increased vascular permeability, leukocyte infiltration, plasma exudation and impaired arterial oxygenation. 5,6 The canonical role of oxidative stress in the development of ALI has been established.…”
mentioning
confidence: 99%
“…In pediatric patients with ALI, higher plasma levels of PAI-1 were associated with increased mortality and fewer ventilator-free days in ALI (10). Another study reported that genetic polymorphisms of peptidase inhibitor 3 (elafin) were associated with increased risk of developing ARDS, especially with extrapulmonary injury (11). Patients with these single nucleotide polymorphisms had lower elafin levels in the plasma, which might reduce host defense against neutrophil elastasemediated injury.…”
Section: Genetics and Alimentioning
confidence: 99%